Baseline Susceptibility of Primary HIV-2 to Entry Inhibitors - Borrego, P (2016)
BACKGROUND: The baseline susceptibility of primary HIV-2 to maraviroc (MVC) and other entry inhibitors is currently unknown. METHODS: The susceptibility of 19 HIV-2 isolates obtained from asymptomatic and AIDS patients and seven HIV-1 clinical isolates to the fusion inhibitors enfuvirtide (ENF) and T-1249, and to the coreceptor antagonists AMD3100, TAK-779 and MVC, was measured using a TZM-bl cell-based assay. The 50% inhibitory concentration (IC(50)), 90% inhibitory concentration (IC(90)) and dose-response curve slopes were determined for each drug. RESULTS: ENF and T-1249 were significantly less active on HIV-2 than on HIV-1 (211- and 2-fold, respectively). AMD3100 and TAK-779 inhibited HIV-2 and HIV-1 CXCR4 tropic (X4) and CCR5 tropic (R5) variants with similar IC(50) and IC(90) values. MVC, however, inhibited the replication of R5 HIV-2 variants with significantly higher IC(90) values (42.7 versus 9.7 nM; P<0.0001) and lower slope values (0.7 versus 1.3; P<0.0001) than HIV-1. HIV-2 R5 variants derived from AIDS patients were significantly less sensitive to MVC than variants from asymptomatic patients, this being inversely correlated with the absolute number of CD4(+) T-cells. CONCLUSIONS: T-1249 is a potent inhibitor of HIV-2 replication indicating that new fusion inhibitors might be useful to treat HIV-2 infection. Coreceptor antagonists TAK-779 and AMD3100 are also potent inhibitors of HIV-2 replication. The reduced sensitivity of R5 variants to MVC, especially in severely immunodeficient patients, indicates that the treatment of HIV-2-infected patients with MVC might require higher dosages than those used in HIV-1 patients, and should be adjusted to the disease stage.